2013
DOI: 10.1016/j.ijdevneu.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to low mercury chloride concentration induces object recognition and aversive memories deficits in rats

Abstract: This work examines the effects of chronic exposure to low inorganic mercury (mercury chloride, HgCl(2)) concentration on the recognition and aversive memories. Forty male Wistar rats were divided into 4 groups treated during 30 or 60 days with saline (control) or HgCl(2) doses. After treated the animals were tested considering object recognition and inhibitory avoidance behavioral memory paradigms. Elevated plus maze, open field and tail flick tests were used to assess anxiety, locomotor and exploratory activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…Studies have reported that the exposure to HgCl 2 is able to induce behavioral alterations during brain developmental periods and, more recently, in adult rats . In the present study, utilizing the two behavioral tests, we verified that the motor function, muscular strength and size, and cerebellar function were damaged in young rats exposed to Hg.…”
Section: Discussionsupporting
confidence: 81%
“…Studies have reported that the exposure to HgCl 2 is able to induce behavioral alterations during brain developmental periods and, more recently, in adult rats . In the present study, utilizing the two behavioral tests, we verified that the motor function, muscular strength and size, and cerebellar function were damaged in young rats exposed to Hg.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, the bran effect-response to mercury seems to be dependent on reaching a critical threshold concentration/deposition after prolonged exposure, since we did not find LH reduction after 30-days exposure. This hypothesis is supported by a recent publication of our group in which we observed that only exposure for 60 days to HgCl 2 in adulthood can cause deleterious effects on cognitive function and memory formation [38]. However, further experiments are still necessary to determine the time necessary for the effects we observed.…”
Section: Discussionsupporting
confidence: 81%
“…In fact, the motor function of rats was compromised after exposure to iHg, as demonstrated by the negative geotaxis and beaker test (Moraes-Silva et al, 2014). Moreover, the chronic exposure to iHg can impair memory formation in rats, leading to a deficit on object recognition and aversive memories (Mello-Carpes et al, 2013). Fish exposure to iHg provided contrasting results, namely on the Atlantic salmon where no alterations were found on overall activity (Berntssen et al, 2003), while Pomatoschistus microps exhibited a reduced ability to swim (Vieira et al, 2009).…”
Section: Introductionmentioning
confidence: 99%